Contrastive Study of Universal quantifiers in Spanish and their Counterparts in Chinese - Shi, Hui (Sinología hispánica. China Studies Review, 2026)
Within the range of quantifiers, universal quantifiers form a special part, since they express the totality of units. There are three universal quantifiers in Spanish: todo/a(s), cada and ambo/as. Thus, the main aim of this paper is to carry out a contrastive study of the three words in Spanish and their counterparts in Mandarin Chinese from syntactic and semantic perspectives by examining the data from the reviewed literature, from two corpora, CORPES (Corpus del Español del Siglo XXI) of Spanish and BCC (BLCU Corpus Center) of Chinese, and from introspection. After taking a brief look at the different opinions of the frequent use of the word 都 dōu in universal quantification sentences and stating the starting point of this article, we perform the comparative analysis one by one and grasp the similarities and differences of the universal quantifiers in Spanish and their counterparts in Mandarin Chinese. In addition, a look at some particular forms that express universal quantification in Mandarin Chinese is offered.